THE LANDSCAPE FROM CHILDHOOD: PLACE AND SPASE IN MODERN UKRAINIAN LITERATURE FOR CHILDREN - Kachak, T. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article outlines the features artistic representation of the place and space in modern Ukrainian texts for children. The landscape from childhood – not only geographically, but also cultural and aesthetic categories. The environmental where the child grows and develops – one aspect of identity formation, its ideology, national identity, mentality. The realistic text’s art world is filled real, concrete (which can be identified), spatial images, toposes, locus. The place events may be associated with childhood memories of the author (autobiographical texts), historical theme (historical fiction), observations (traveling notes, diaries), impressions of the adventure (adventure literature), emotional experiences and contemplation (watercolor, landscape sketches), etc. The abstract, fantastic, imaginary places often symbolic and magical significance and dominated in fiction texts.